Drug-induced lupus erythematosus - Ana L. Gouveia; Margarida Gonçalo (Sociedade Portuguesa de Dermatologia e Venereologia, 2023)
Drug-induced lupus erythematosus is an autoimmune disease with unexpected onset after treatment with certain drugs. Clinically, this disease is very similar to idiopathic lupus erythematosus, although its manifestations are typically milder. In addition, the laboratory and histological changes of the induced forms are also not significantly different from the idiopathic condition, sometimes making the diagnosis of the drug-induced form a challenge for clinicians. This entity has been gaining relevance in the clinical setting and the number of drugs associated with it has been increasing, mainly due to the emergence of new biological therapies with a strong causal link with drug-induced lupus, such as tumor necrosis factor-alpha inhibitors. However, there are still no universally accepted diagnostic criteria to identify this disease, and information about its pathophysiology is still somewhat scarce, making it difficult to predict the most likely culprit drugs before there are enough reports to establish a strong link. In addition, although some risk factors have shown susceptibility for certain individuals, they are not yet fully understood. Given the possibility of disease reversal by the withdrawal of the offending drug, it is extremely important to be aware of the possible implication of a drug in the pathogenesis of this disease, and for clinicians who approach patients with lupus manifestations, particularly cutaneous manifestations, it is mandatory to look for the onset of new drugs used by the patient. This review will systematize the current knowledge about this drug-induced lupus, in terms of pathophysiology, clinical, histopathological, and laboratory manifestations, diagnosis, and treatment, as well as the most commonly implicated drugs.